Tracking Javanese Traditional Arts in North Sumatra 1900-1930s - Ririn Darini; Nanang Setiawan; Muhammad Yuanda Zara; Agus Murdiyastomo (Universitas Islam Negeri Sumatera Utara, 2026)
Until now, several traditional Javanese arts such as ketoprak, horse braids, and wayang orang can be found in North Sumatra. This research aims to find out why and how Javanese traditional art can develop in this region. The method used in this research is a historical method which includes 4 research stages, namely heuristics, criticism, interpretation and historiography. The research results show that traditional Javanese art has been present in North Sumatra since the colonial era because of Javanese migrants who were employed on foreign plantations. They brought with them Javanese cultural heritage in the form of performing arts, such as gamelan, ketoprak, wayang orang, and dances. This traditional art was deliberately given a place by plantation entrepreneurs to make their workers feel at home. In its development, this traditional art not only functions as a form of entertainment and expression of cultural identity, but also as a tool to maintain collective spirit and solidarity amidst harsh and often unfair working conditions.